Running rescues a fear-based contextual discrimination deficit in aged mice - Wu, Melody V.; Luna, Victor M.; Hen, Rene (Frontiers in Systems Neuroscience, 2015)
Normal aging and exercise exert extensive, often opposing, effects on the dentate gyrus (DG) of the hippocampus altering volume, synaptic function, and behaviors. The DG is especially important for behaviors requiring pattern separation—a cognitive process that enables animals to differentiate between highly similar contextual experiences. To determine how age and exercise modulate pattern separation in an aversive setting, young, aged, and aged mice provided with a running wheel were assayed on a fear-based contextual discrimination task. Aged mice showed a profound impairment in contextual discrimination compared to young animals. Voluntary exercise rescued this deficit to such an extent that behavioral pattern separation of aged-run mice was now similar to young animals. Running also resulted in a significant increase in the number of immature neurons with tertiary dendrites in aged mice. Despite this, neurogenesis levels in aged-run mice were still considerably lower than in young animals. Thus, mechanisms other than DG neurogenesis likely play significant roles in improving behavioral pattern separation elicited by exercise in aged animals.